2020
DOI: 10.1001/jamacardio.2020.1787
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of QT Intervals in a Case Series of Patients With Coronavirus Disease 2019 (COVID-19) Infection Treated With Hydroxychloroquine Alone or in Combination With Azithromycin in an Intensive Care Unit

Abstract: US Food and Drug Administration. Vyndaquel & Vyndamax (tafamidis).Accessed April 1, 2020. https://www.accessdata.fda.gov/drugsatfda_docs/nda/ 2019/211996Orig1s000,%20212161Orig1s000TOC.cfm 3. Gurwitz JH, Maurer MS. Tafamidis-a pricey therapy for a not-so-rare condition. JAMA Cardiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
276
7
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(328 citation statements)
references
References 6 publications
32
276
7
13
Order By: Relevance
“…The statistically signi cant result showing 2.49 times higher odds of having arrhythmias and signi cant QT prolongation in cases treated with HCQ with/without AZT with SOC (OR 2.49, 95% CI 1.67-3.70). It is in concordance with multiple studies that have shown an increased risk of QT among patients taking hydroxychloroquine [9,10]. Before Mehra et al's paper retraction, when we analysed data including from that paper showed 10 times higher odds of having arrhythmias and signi cant QT prolongation which has also been attached with the other portions of the analysis in the supplementary le [Supplementary le 3] [16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The statistically signi cant result showing 2.49 times higher odds of having arrhythmias and signi cant QT prolongation in cases treated with HCQ with/without AZT with SOC (OR 2.49, 95% CI 1.67-3.70). It is in concordance with multiple studies that have shown an increased risk of QT among patients taking hydroxychloroquine [9,10]. Before Mehra et al's paper retraction, when we analysed data including from that paper showed 10 times higher odds of having arrhythmias and signi cant QT prolongation which has also been attached with the other portions of the analysis in the supplementary le [Supplementary le 3] [16].…”
Section: Discussionsupporting
confidence: 85%
“…Hydroxychloroquine use can give rise to mild non-speci c adverse effects like nausea, vomiting, headache to severe arrhythmias affecting multiple systems [5,8]. QT intervals prolongation is the commonest cardiac consequence of HCQ with drug-like azithromycin (AZT), for which the patient needs to be monitored carefully before other dire consequences like ventricular arrhythmias [9][10][11]. Metabolic derangements like hypoglycemia may also occur as other adverse consequences [12].…”
mentioning
confidence: 99%
“…Despite the fact that HCQ/CQ were commonly used for rheumatoid arthritis and systemic lupus erythematosus in the general population, there has been major concern with widespread use of these medications for COVID-19 due to possible QTc prolongation and induction of life-threatening arrhythmias. There is general consensus that QTc prolongation after HCQ/CQ use may occur in a dose-dependent way [11,[32][33][34][35]. Previous studies demonstrated that HCQ/CQ block the hERG potassium channels, extending ventricular repolarization and action potentials, and hence, may trigger ventricular tachyarrhythmias [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of QTc interval prolongation was higher in patients receiving loop diuretics (adjusted odds ratio [aOR] 3.38; 95% CI 1.03, 11.08) and those with QTc interval ≥450 msec (aOR 7.11; 95% CI 1.75, 28.87).Hydroxychloroquine was discontinued in nine patients due intractable nausea or hypoglycaemia, and in one patient because of torsades de pointes during treatment with hydroxychloroquine plus azithromycin."Clinicians should carefully weigh risks and benefits if considering hydroxychloroquine and azithromycin, with close monitoring of QTc and concomitant medication usage," said the authors.The use of hydroxychloroquine with or without azithromycin increases the QTc interval in the majority of patients with COVID-19 who are in an intensive care unit (ICU), according to findings of a French study published in a research letter in JAMA Cardiology. 2 Forty patients with COVID-19 who were admitted to an ICU in Lyons, France, received hydroxychloroquine alone (55%) or with azithromycin (45%); 50% of patients also received other drugs with a known or possible risk of QTc interval prolongation.Treatment with hydroxychloroquine with or without azithromycin increased the QTc interval in 93% of patients. Overall, QTc interval was prolonged in 36% of patients: the QTc interval increased by ≥60 msec in ten patients and QTc interval prolongation was ≥500 msec in seven patients.…”
mentioning
confidence: 99%
“…The use of hydroxychloroquine with or without azithromycin increases the QTc interval in the majority of patients with COVID-19 who are in an intensive care unit (ICU), according to findings of a French study published in a research letter in JAMA Cardiology. 2 Forty patients with COVID-19 who were admitted to an ICU in Lyons, France, received hydroxychloroquine alone (55%) or with azithromycin (45%); 50% of patients also received other drugs with a known or possible risk of QTc interval prolongation.…”
mentioning
confidence: 99%